An update on oligosaccharides and their esters from traditional chinese medicines: chemical structures and biological activities. - Xiang Yang Chen; Wang, Ru-Feng; Liu, Bin (Evid Based Complement Alternat Med, 2015)
A great number of naturally occurring oligosaccharides and oligosaccharide esters have been isolated from traditional Chinese medicinal plants, which are used widely in Asia and show prominent curative effects in the prevention and treatment of kinds of diseases. Numerous in vitro and in vivo experiments have revealed that oligosaccharides and their esters exhibited various activities, including antioxidant, antidepressant, cytotoxic, antineoplastic, anti-inflammatory, neuroprotective, cerebral protective, antidiabetic, plant growth-regulatory, and immunopotentiating activities. This review summarizes the investigations on the distribution, chemical structures, and bioactivities of natural oligosaccharides and their esters from traditional Chinese medicines between 2003 and 2013.